Transition to dental practice: Newly graduated dentists' views of being successful in dental practice. (17th July 2020) - Leadbeatter, Delyse; Madden, Jacalyn; Ross, Benjamin; Russell, Elara
Abstract: Background: The transition of dental graduates to the workforce is of interest to dental educators. The ways dentists think about success and successful practice tend to be tied to business parameters, patient flow and job satisfaction. These measures are narrow, however, and there is scant literature exploring success in ways that connects with professional identity formation. This study aims to add to scholarly understanding about the experiences of newly graduated dentists by asking: What is the variation in the ways new graduate dentists experience success in practice? Methods: The qualitative methodology used in this study is phenomenography. Phenomenography studies the variation in the way a group of people experience a common phenomenon. In‐depth, semi‐structured interviews were conducted with 12 new dentists who had graduated from the University of Sydney. Results: Five increasingly sophisticated, qualitatively distinct categories of description were identified: the day runs smoothly, keeping busy, providing quality patient care, generating personal meaning and having a sense of connection and belonging. Conclusions: This study gives insights into the complex ways newly graduated dentists think about successful dentistry. It broadens our view of successful practice beyond commercial aspects to include practitioner identity. Importantly, sense of responsibility, the practice environment and mentorship emerge as key players in this transitional career stage.